2016
DOI: 10.1159/000446117
|View full text |Cite
|
Sign up to set email alerts
|

Global Epidemiology of Head and Neck Cancers: A Continuing Challenge

Abstract: Background: Head and neck cancers (HNCs) continue to remain a significant public health burden worldwide, causing significant mortality and morbidity despite significant clinical advances enabling their early diagnosis and treatment. Methods: We used data from the GLOBOCAN 2012, Cancer Incidence in Five Continents, World Health Organization Mortality Database and Surveillance, Epidemiology, and End Results programmes to describe the current epidemiology of HNCs. Results: Estimated age-standardised incidence/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
253
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(291 citation statements)
references
References 37 publications
(38 reference statements)
4
253
0
11
Order By: Relevance
“…This number is expected to grow significantly in the coming decades, resulting in increased demand for treatment 2 …”
Section: Introductionmentioning
confidence: 99%
“…This number is expected to grow significantly in the coming decades, resulting in increased demand for treatment 2 …”
Section: Introductionmentioning
confidence: 99%
“…Although lip and oral cavity cancer accounts for less than 3% of all cancer cases worldwide, its low survival rate and adverse consequences on quality of life have garnered it to be considered as a significant public health problem; in fact, two thirds of its burden occurs in developing countries (Costa et al, 2016;Farah et al, 2014;Global Burden of Disease Cancer, 2015;Ribeiro et al, 2015;Torre et al, 2015;Warnakulasuriya, 2009 Since people who live in developing countries are exposed to a wider range of risk factors for cancer of the lip and oral cavity, the highest incidence rates are reported from these countries (Byakodi et al, 2012;de Camargo Cancela et al, 2010;Gupta et al, 2016;Rastogi et al, 2004). The most important risk factors of this cancer are tobacco use, alcohol, chewing tobacco, betel quid, poor eating habits, sun exposure, viral infections (especially HPV), and poor oral hygiene (de Camargo Cancela et al, 2010;Farah et al, 2014;Funk et al, 2002;Ribeiro et al, 2015;Warnakulasuriya, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the incidence of lip and oral cavity cancer is higher in people with lower education and income (de Camargo Cancela et al, 2010;Farah et al, 2014;Jayalekshmi et al, 2009;Johnson et al, 2010;Ribeiro et al, 2015;Swaminathan et al, 2009). People with less education are at greater risk of lip and oral cavity cancer due to less awareness of cancer risk factors, poor sanitary habits, greater consumption of alcohol and tobacco, and use of chewing tobacco (Gupta et al, 2016;Hashibe et al, 2003;Videnovic et al, 2016;Warnakulasuriya, 2009). Also, people with less income are more likely to have this type of cancer due to limited access to dental care, poor oral hygiene, consumption of fewer fruits and vegetables, greater HPV risk, and less protection against the sun (Arnold et al, 2016;Farah et al, 2014;Guha et al, 2007;Johnson et al, 2010;Monteiro et al, 2013;Morris et al, 2000;Pavia et al, 2006 (Conway et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Men are afected signiicantly more than women [51]. Head and neck cancer includes cancers of the mouth, nose, sinuses, salivary glands, throat, and lymph nodes in the neck.…”
Section: Overviewmentioning
confidence: 99%